2012
DOI: 10.3748/wjg.v18.i11.1235
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of theTLR2andTLR4genes are associated with risk of gastric cancer in a Brazilian population

Abstract: Our data indicate that TLR2 -196 to -174 del and TLR4+896G may increase the risk of gastric cancer in a Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 38 publications
2
73
1
Order By: Relevance
“…The products were electrophoresed on 3% agarose gel. Polymorphisms at TLR2-196 to -174 del were investigated using the PCR method following the procedures described by de Oliveira et al (11). Products were examined by electrophoresis in 1.5% agarose gel.…”
Section: Analysis Of the Tlr2 Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The products were electrophoresed on 3% agarose gel. Polymorphisms at TLR2-196 to -174 del were investigated using the PCR method following the procedures described by de Oliveira et al (11). Products were examined by electrophoresis in 1.5% agarose gel.…”
Section: Analysis Of the Tlr2 Polymorphismsmentioning
confidence: 99%
“…Brown et al (9) reported that this mutation may abrogate TLR2 signaling in response to human cytomegalovirus. Furthermore, the -174 to -196 del of TLR2 gene polymorphisms may confer an increased susceptibility to breast cancer development (10), gastric cancer (11) and prostate cancer (12). Therefore, the present study aimed to investigate the frequencies of TLR2 gene polymorphisms (Arg677Trp, Arg753Gln and the -196 to -174 del) in patients with gout and explore the association between the polymorphisms and the susceptibility to gout in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TLR2 rs3804099 and rs3804100 were not significantly associated with decreased risk of H. pylori susceptibility, precancerous gastric lesions and/or GC development in this study. Furthermore, TLR4 rs4986790 has been shown to promote and protect against GC development in a Brazilian population (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Asp299Gly and Thr399Ile polymorphisms have been reported to be associated with different diseases such as gastric cancer, hepatitis C virus-induced hepatocellular carcinoma, Crohn's Disease and ulcerative colitis [16,52,53], supporting a functional role for these polymorphisms. Also, these two polymorphisms seem to modify the pattern of inflammatory cytokines and chemokines in the gastric mucosa, suggesting a contribution to the clinical outcome of H. pylori infection [54].…”
Section: Citationmentioning
confidence: 99%